Gaya Kepemimpinan Transformasional Kepala Ruang dan Self Efficacy Perawat di Ruang Rawat Inap Rsud Dr. R. Goeteng Taroenadibrata Purbalingga - Tri Sumarni; Arni Nur R; Wasis Eko K (Malahayati Nursing Journal, 2022)
ABSTRACT Self-efficacy influences nurses' motivation to care, thinking and decision-making processes, prioritizing interventions and encouraging them to continue caring for patients despite difficulties and failures. Self-efficacy is developed in four ways, which include the experience of success, the experience of others, emotional management and verbal persuasion. The head of the room can provide an increase in nurse self-efficacy through verbal persuasion in the hospital. The purpose of this study was to analyze the relationship between transformational leadership style and nurses' self-efficacy. This research is a descriptive correlational study with a cross sectional approach. The sample size in this study was calculated based on the Slovin formula. The number of samples in this study were 92 nurses who were taken by purposive sampling technique. The instruments in this study were the Global Transformational Leadership (GTL) and New General Self-Efficacy (NGSE) questionnaires. The GTL AND NGSE questionnaires were measured in the form of a Likert scale, 5 points ranging from 1 strongly disagree to 5 strongly agree. Data analysis using Spearman Rank statistical test. The average transformational leadership style is 25.54, the average self-efficacy is 34.14, there is a relationship between transformational leadership style and self-efficacy (r=0.76, p=0.000).  There is a relationship between transformational leadership style and nurses' self-efficacy. Transformational leadership pays attention to the needs of subordinates, inspires subordinates' motivation and advances their skills. These behaviors have a positive impact on the self-efficacy of subordinates. Keywords: Self Efficacy; Transformational Leadership Style  ABSTRAK Self efficacy mempengaruhi motivasi perawat untuk merawat, proses berpikir dan pengambilan keputusan, memprioritaskan intervensi dan mendorong untuk terus merawat pasien meskipun mengalami kesulitan dan kegagalan. Self-efficacy dikembangkan dalam empat cara, yang meliputi pengalaman keberhasilan, pengalaman orang lain, pengelolaan emosi dan persuasi verbal. Kepala ruang dapat memberikan peningkatan self-efficacy perawat melalui adanya persuasi verbal di rumah  sakit. Tujuan dari penelitian ini untuk menganalisis hubungan gaya kepemimpinan transformasional dengan self efficacy perawat.  Penelitian ini merupakan penelitian deskriptif korelasional dengan pendekatan cross sectional. Besar sampel pada penelitian ini dihitung berdasarkan rumus Slovin. Jumlah sampel dalam penelitian ini adalah 92 perawat pelaksana yang diambil dengan teknik purposive sampling. Instrumen dalam penelitian ini yaitu kuesioner Global Transformational Leadership (GTL) dan  New General Self-Efficacy (NGSE). Kuesioner GTL DAN NGSE diukur dalam bentuk skala likert, 5 point mulai dari 1 sangat tidak setuju sampai 5 sangat setuju. Analisis data menggunakan uji statistik Spearman Rank.    Rata-rata gaya kepemimpinan transformasional 25,54, rata-rata self efficacy 34,14 ada hubungan gaya kepemimpinan transformasional dengan self efficacy (r=0,76, p=0,000). Terdapat hubungan antara gaya kepemimpinan transformasional dengan self efficacy perawat.  Kepemimpinan transformasional memperhatikan kebutuhan bawahan, menginspirasi motivasi bawahan dan memajukan keterampilan mereka. Perilaku-perilaku tersebut memiliki dampak positif pada efikasi diri bawahan. Kata kunci: Self Efficacy; Gaya Kepemimpinan Transformasional